Antioxidant Activity Evaluation from Tomatoes’ N-Hexane, Ethyl Asetate, and Water Fraction with DPPH - Ratna Sari Dewi; Desy Ayu Irma Permatasari; Tatiana Siska Wardani; Muladi Putra Mahardika (Universitas Muhammadiyah Yogyakarta, 2022)
Antioxidants are compounds that can stabilize free radicals in the body. Free radicals are highly reactive molecules as they have unpaired electrons to interact with body cell molecules. Tomatoes contain flavonoids, saponins, solanine tannins, folic acid, malic acid, citric acid, protein, fat, vitamins, minerals, and histamine, which can be used as antioxidants. This study aims to evaluate the antioxidant activity of n-hexane, ethyl acetate, water fraction, and ethanol extracts of Tomatoes and to determine the greatest antioxidant activity between n-hexane, ethyl acetate, water and vitamin C. Tomatoes (Lycopersicum esculentum Mill.) was extracted using the maceration method with ethanol followed by fractionation using n-hexane and ethyl acetate solvents. The test of antioxidant activity to DPPH radical was conducted on n-hexane, ethyl acetate, water, and vitamin C. The antioxidant activity results, expressed by IC50 value to the n-hexane, ethyl acetate, water fraction of Tomatoes fruit, were 4.4603 ppm; 4.0868 ppm; and 4.0527 ppm, respectively. Thus, the greatest antioxidant activity was the water fraction.